Five little pigs : a Hercule Poirot novel - Christie, Agatha, 1890-1976. (New York : Berkley Books, 1984)
Carla Crale, convinced her mother is innocent of the murder of her father, a crime for which the woman was sentenced to life in prison, challenges brilliant Belgian sleuth Hercule Poirot to clear her mother's name by returning to the scene of the crime.
"Also published as Murder in retrospect.".
Young Adult
Keywords: Murder -- Fiction; Poirot, Hercule (Fictitious character) -- Fiction; Private investigators -- England -- Fiction; Homicide -- Fiction; Mystery fiction; Poirot, Hercule (Fictional character) -- Fiction; Private investigators -- Fiction; England -- Fiction; England -- Fiction